2019
DOI: 10.1016/j.jtho.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of a Novel PRKCB-ALK, EML4-ALK Double-Fusion in a Lung Adenocarcinoma Patient and Response to Crizotinib

Abstract: ND, not detected; c.HGVS, description of coding DNA (c.) varients by human genome variation society (HGVS); p.HGVS, description of protein (p.) varients by HGVS. *describe a stop codon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
(5 reference statements)
1
15
0
Order By: Relevance
“…A few cases of co-existence of canonical and non-canonical ALK fusions has been reported in recent studies (29,30); however, its clinical relevance was largely unknown. We found that there were little differences in PFS after crizotinib treatment among different ALK fusion groups, whereas patients with complex ALK fusions had better OS.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of co-existence of canonical and non-canonical ALK fusions has been reported in recent studies (29,30); however, its clinical relevance was largely unknown. We found that there were little differences in PFS after crizotinib treatment among different ALK fusion groups, whereas patients with complex ALK fusions had better OS.…”
Section: Discussionmentioning
confidence: 99%
“…Curation of PKC gene fusions 5' and 3' PKC fusions organized in Table S1, Table S2, and graphed in Figure 1, B and C were curated from the literature (18,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) and the following online databases: the Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer (mitelmandatabase.isb-cgc.org), the TCGA Tumor Fusion Gene Data Portal, ChimerDB v3.0, and COSMIC (cancer.sanger.ac.uk) (30,(38)(39)(40). Fusions were detected in the following cancer types: BFH, bladder urothelial carcinoma, BRCA, cervical squamous cell carcinoma and endocervical adenocarcinoma, colon adenocarcinoma, lymphoid neoplasm diffuse large B-cell lymphoma, esophageal carcinoma, glioblastoma multiforme, head and neck squamous cell carcinoma, clear cell renal cell carcinoma, kidney renal papillary cell carcinoma, acute myeloid leukemia, LGG, liver hepatocellular carcinoma, LUAD, LUSC, medulloblastoma, ovarian serous cystadenocarcinoma, pheochromocytoma and paraganglioma, PGNT, prostate adenocarcinoma, sarcoma, skin cutaneous melanoma, stomach adenocarcinoma, T-cell acute lymphoblastic leukemia, and UCEC.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the landscape of PKC fusions in cancer, we queried the literature and several online databases to curate a comprehensive list of all PKC gene fusions identified from patient tumor samples (Table S1) (18,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The online databases utilized in this study include the Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer, the TCGA Tumor Fusion Gene Data Portal, ChimerDB v3.0, and the Catalogue of Somatic Mutations in Cancer (COSMIC) (30,(38)(39)(40).…”
Section: A Multitude Of Pkc Fusions Have Been Identified In Cancermentioning
confidence: 99%
“…We retrospectively analyzed genomic profiling data of 1,312 patients with rare tumors from Geneplus database. This database contained patients enrolled from multiple hospitals of China from September 2015 to October 2019 (18,19). All patients received next-generation sequencing (NGS) testing in Geneplus-Beijing Institute after obtaining written informed consent.…”
Section: Patient Recruitmentmentioning
confidence: 99%